2022
DOI: 10.15252/embj.2022111648
|View full text |Cite
|
Sign up to set email alerts
|

An accessory prefrontal cortex–thalamus circuit sculpts maternal behavior in virgin female mice

Abstract: The ability to care for the young is innate and readily displayed by postpartum females after delivery to ensure offspring survival. Upon pup exposure, rodent virgin (nulliparous) females also develop parental behavior that over time becomes displayed at levels equivalent to parenting mothers. Although maternal behavior in postpartum females and the associated neurocircuits are well characterized, the neural mechanisms underlying the acquisition of maternal behavior without prior experience remain poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Chemically targeted activation with simultaneous calcium imaging of neurons was conducted using AAVs containing a Cre-dependent DREADD 55 , 56 construct (AAV-DIO-CAG-hM3Dq-2A-dTomato; Addgene #202036) added to organotypic hippocampal slice cultures of Prox1-cre::Ai95 (GCaMP6f) mice at 4–6 d in vitro. Each transduced cell expressed both cytoplasmic dTomato and the excitatory designer receptor hM3Dq.…”
Section: Methodsmentioning
confidence: 99%
“…Chemically targeted activation with simultaneous calcium imaging of neurons was conducted using AAVs containing a Cre-dependent DREADD 55 , 56 construct (AAV-DIO-CAG-hM3Dq-2A-dTomato; Addgene #202036) added to organotypic hippocampal slice cultures of Prox1-cre::Ai95 (GCaMP6f) mice at 4–6 d in vitro. Each transduced cell expressed both cytoplasmic dTomato and the excitatory designer receptor hM3Dq.…”
Section: Methodsmentioning
confidence: 99%
“…A second study, using retrograde AAVs, reported an incredibly sparse population of ACA neurons (1–3 neurons per section) that projected monosynaptically to both dorsal and ventral CA1 ( Bian et al, 2019 ). However, other mouse studies using anterograde AAVs to map efferents from ACA report no projection to hippocampus ( Glat et al, 2022 ; Shi et al, 2022 ). While not reported explicitly, representative images from another study mapping outputs of ACA revealed no labelling in hippocampus ( Zhang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 98%
“…The formation and density of dendritic spines in hippocampal neurons [ 167 , 214 , 216 219 ], as well as neurogenesis in the dentate gyrus [ 220 ], and long-term potentiation [ 221 ], are further molded by estradiol. Increased levels of estradiol are known to specifically affect brain areas directly related to maternal care behavior [ 222 ], such as the medial preoptic area (mPOA) [ 223 ], amygdala [ 224 ], hypothalamus [ 225 , 226 ], olfactory system [ 227 , 228 ], parietal, and prefrontal cortex [ 168 ].…”
Section: Introductionmentioning
confidence: 99%